How to Teach Make Up for The Beginner in ATMAISWARI - Asri Wibawa Sakti; Rasi Yugafiati; Tri Karyono; Mally Maeliah (Universitas Sebelas Maret, 2019)
The article aims to discuss about how to teach make up for the beginner through an organized event. The researcher explains about step by step to make a great event such as AISMAWARI. The research is descriptive qualitative. The researcher describes the study briefly. The researcher posts and analizes, and explains the pictures briefly from pre-event, the main event, and the post event. The research reveals the phenomenon that collaboration is needed to make a big events. It also collaborates with a hundred of make up artists, a hundred of designers, and a hundred of models. It involves many supporters. It is held at Atrium Istana Plaza Bandung, in Pasir Kaliki Street no. 121-123. The due date is March 8th, 2019. It related to the primary education pedagogy. It is because the researcher tries to teach the beginner although it is covered by multiliteracy and multiagendas in a big events. The goal is to ask the participants or beginners to think in higher level. The researcher wants to educate the beginner not only to hear the material, but also do the action. As it is believed, practices make perfect.